PERANAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) TERHADAP ANAK KORBAN PENCABULAN - Fadesha Lucia Martina; Wirna Rosmelly (UNES Journal of Swara Justisia, 2018)
Sexual violence against children is not only happening in big cities, but has reached the remote or rural areas. This means that this phenomenon has become a social and legal problem that needs to get special attention. Law enforcement against the perpetrators need to be considered. Sawahlunto has occurred sexual abuse against children by children. This condition is clearly very apprehensive amid the government's efforts to combat the crime of sexual violence against children. With these facts, community participation is increasingly important and fundamental as a place of assistance to children and women who experience major social problems concerning violations of human rights or sexual violence as mandated by the State Minister of Women's Empowerment and Child Protection No. 6 of 2015 on the System Women's Empowerment and Child Protection.